2009
DOI: 10.1007/s10704-009-9354-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of crack interactions at adjacent holes and onset of multi-site fatigue damage in aging airframes

Abstract: Focusing on the geometry of one hot spot in airframes, this paper discusses the onset of the interaction of two collinear cracks at adjacent holes and defines the onset as a criterion for multi-site fatigue damage failure. The finite element method is used to calculate the stress intensity factors at the tips of two collinear cracks at adjacent holes growing towards each other. The stress intensity factor is found to increase rapidly at the onset of interaction. Since a rapid increase in stress intensity facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…As for the conditions of 21 and 29 mm, there were no actual differences between the average RTS of CC and NCC based on the statistical analysis. The average ultimate tensile strength σ of the specimen without MSD was 456.0 MPa, the average RTS of MSD specimens σ' compared with that without MSD decreased 46.4% (CC21), 43.3% (CC25), 42.0% (CC29), 45.9% (NCC21), 42.1% (NCC25), and 41.0% (NCC29) respectively which were calculated by Equation (5). Moreover, the RTS decrease percentage (pct) of CC21 was larger than that of NCC21, similar decreasing trends were observed in other CC and NCC, which contain the following relationship: pctCC21 > pctNCC21 > pctCC25 > pctNCC25 > pctCC29 > pctNCC29.…”
Section: Dic Strain Nephogrammentioning
confidence: 99%
See 1 more Smart Citation
“…As for the conditions of 21 and 29 mm, there were no actual differences between the average RTS of CC and NCC based on the statistical analysis. The average ultimate tensile strength σ of the specimen without MSD was 456.0 MPa, the average RTS of MSD specimens σ' compared with that without MSD decreased 46.4% (CC21), 43.3% (CC25), 42.0% (CC29), 45.9% (NCC21), 42.1% (NCC25), and 41.0% (NCC29) respectively which were calculated by Equation (5). Moreover, the RTS decrease percentage (pct) of CC21 was larger than that of NCC21, similar decreasing trends were observed in other CC and NCC, which contain the following relationship: pctCC21 > pctNCC21 > pctCC25 > pctNCC25 > pctCC29 > pctNCC29.…”
Section: Dic Strain Nephogrammentioning
confidence: 99%
“…Multi-site damage (MSD) is a special kind of failure that is commonly found in aging aircraft structures, it leads people to realize what is called the aging aircraft problem, which has developed into the main concern for research on airframe strength [4]. Experiments revealed that the design of the fuselage may affect the ultimate failure type of longitudinal lap joints in the case of MSD [5][6][7][8]. The effects of overloading, under-loading and bending on MSD were examined.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Chang and Kotousov recently used the classical strip yield model and plasticity induced crack closure concept to develop and experimentally validate a new computational technique for the evaluation of interactions between through cracks. Wang, Modarres and Hoffman used the Finite Element method to evaluate K at the tips of two collinear through cracks at adjacent holes and proposed a criterion to determine when crack growth is influenced by mutual interactions.…”
Section: The Crack Growth Modelmentioning
confidence: 99%
“…The trend of operating aircraft up to or even exceeding their design lives has raised concerns on the airframe structural integrity due to fatigue failures, which often involve multiple cracks [31][32][33][34]. Experiments and numerical studies conducted by Iida [35], Iida and Kawahara [36], Wang et al [37], Frise and Bell [38], Leek and Howard [39], and Kamaya [40], which were mainly on long crack coalescence showed that the effects of interaction amongst closely spaced cracks can significantly influence the rate of coalescence, and hence, accelerating the crack growth rates. This will in turn potentially affect the overall fatigue life of engineering structures.…”
Section: Introductionmentioning
confidence: 99%